Therapeutic hypothermia as a neuroprotective strategy in newborns with perinatal asphyxia—case report - Oliveira, Nayara Rodrigues Gomes de; Teixeira, Gustavo Gonçalves; Fernandes, Kathlen Terezinha Montes Soares; Avelar, Marla Moreira; Medeiros, Maja; Formiga, Cibelle Kayenne Martins Roberto (Frontiers in Rehabilitation Sciences, 2023)
Perinatal asphyxia is a public health problem and the third major cause of death among children under five years old. Objective: Report two clinical cases of newborns with perinatal asphyxia submitted to therapeutic hypothermia and the follow-up of their motor development after hospital discharge. Methods: This retrospective case report study included two newborns with hypoxic-ischemic encephalopathy due to perinatal asphyxia who received a hypothermia protocol at the neonatal intensive care unit (NICU). The two newborns and their families were followed up at the outpatient clinic and assessed using the Hammersmith Child Neurological Examination, Alberta Child Motor Scale, and Denver Developmental Screening Test-II. Results: The newborns were submitted to a 72-hour hypothermia protocol. One newborn remained for 13 days in the NICU, while the other remained for 22 days. According to the multidisciplinary team, both cases presented typical motor development with no cerebral palsy during the follow-up. Conclusion: Both cases showed positive results and a good prognostic for motor development. The therapeutic hypothermia may be a strategy to prevent neurologic sequelae in newborns with perinatal asphyxia, including cerebral palsy.